Analysis of pressure oscillation and structural parameters on the performance of deflector jet servo valve - Hazem K. Abdallah; Jinghui Peng; Songjing Li (Alexandria Engineering Journal, 2023)
The performance of deflector jet servo-valve is highly affected by the flow field characteristics in the pilot stage of the deflector jet servo-valve. This research used the large eddy simulation method to study the pressure pulsation characteristics of the front stage flow field of DJSV, which has a high significance for the reasonable design of DJSV and the suppression of self-excited oscillation. The geometric model of the three-dimensional flow field of the jet pilot stage of the servo valve deflection plate was established. LES method was used to analyze the influence of the geometric parameters of the jet outlet, amplifier and receiving port on the flow field distribution characteristics of the pre-stage. The results show that pressure oscillation is highly affected by the inlet pressure. Structure optimization is a good solution for decreasing pressure oscillation in deflector jet servo valve.